Augmenting the training space of an epidural needle insertion simulator with HoloLens - da Silva, Daniel; Costa, Cátia Botelho; da Silva, Nuno André; Ventura, Isabel; Leite, Francisca Pais; Lopes, Daniel Simões (Computer methods in biomechanics and biomedical engineering., 2022)
The goal of this study is to explore the potential of the Optical See-Through Augmented Reality (OST-AR) in the training of median and paramedian epidural anaesthesia administration. To this end, we propose EpiduralLens, an epidural needle insertion simulator that augments the training space by resorting to a dummy, a HoloLens, an AR target, 3D sound feedback, and voice commands. The proposed system projects relevant 3D anatomical information and visual guides that are placed on and around the dummy, which are complemented with aural feedback that guides the instruction process. EpiduralLens was evaluated by 6 anaesthesiologists. The results of the formal evaluation sessions indicate that our prototype had high acceptability by the experts, verifying that combining an aural interface with 3D visual interface is a useful way to aid immersion and improve the learnability of trainees. Moreover, the participants showed interest in using the application in future sessions as a training aid for median and paramedian epidural anaesthesia administration.